Development of Tourism in The South Coastal of Special Region of Yogyakarta - Noto Pamungkas; Rusherlisyani Rusherlisyani; Raden Hendri Gusaptono; Latifah Dianing Putri; Ulfah Rahmawati; Adiwirastu Nuralamsyah; Aryani Muji Kirana Putri (Eksos LPPM, 2020)
Indonesia has a long coastline with a length of 81,000 km and stretches along its coastal area which has various potentials that can be utilized for sustainable development. Therefore, in the presence of several potentials found in the coastal region, it occurs in the coastal area of the Special Region of Yogyakarta where it has several potential coastal tourism that can be developed. But in its development, various kinds of problems arise related to its coastal area. These problems if not followed up will affect the sustainability and existence of coastal tourism. Based on this, the research aims to provide direction for the development of coastal tourism in Yogyakarta in realizing the sustainability of coastal areas in the form of development concepts, policies and management and regional financing. The research approach used in this study is quantitative and qualitative approaches. The qualitative approach in this study was carried out in mapping potential and problems and conditions that existed in the area in determining the direction of coastal tourism development in Yogyakarta through descriptive analysis methods. While the quantitative approach taken is in determining priority locations that will be developed as coastal tourism in Bantul Regency, Kulon Progo Regency and Gunung Kidul Regency by looking at its sustainability through scoring and weighting methods